2017
DOI: 10.1055/s-0043-120268
|View full text |Cite
|
Sign up to set email alerts
|

Memantine Augmentation Improves Symptoms in Serotonin Reuptake Inhibitor-Refractory Obsessive-Compulsive Disorder: A Randomized Controlled Trial

Abstract: Memantine is an effective and well-tolerated augmentation in severe OCD patients refractory to SRI monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Promising results from placebo-controlled studies concerning the efficacy of add-on treatments with memantine [272][273][274] and N-acetylcysteine [275][276][277] (however, the latter showed some inconsistencies [278]) need replication.…”
Section: Other Medicationsmentioning
confidence: 99%
“…Promising results from placebo-controlled studies concerning the efficacy of add-on treatments with memantine [272][273][274] and N-acetylcysteine [275][276][277] (however, the latter showed some inconsistencies [278]) need replication.…”
Section: Other Medicationsmentioning
confidence: 99%
“…Current first-line treatments for OCD include exposure and response prevention (ERP) and serotonin reuptake inhibitors (SRIs; Sookman and Fineberg, 2015). However, as not all patients respond satisfactorily to these treatments, other augmenting drugs (such as glutamate-modulating agents, among others) may need to be added to SRIs (Fineberg et al, 2006; Simpson et al, 2013; Modarresi et al, 2018). Clearly, to develop more effective treatments for OCD, a greater understanding of its etiology and pathophysiology is required.…”
Section: Introductionmentioning
confidence: 99%
“…These findings describing the role of glutamate and its transporters in OCD psychopathology have raised the possibility of clinical value of glutamate modulators in treating OCD (Pittenger et al, 2006;Grados et al, 2013). In support of this, the voltage-sensitive Na 1 channel blocker that prevents glutamate release, riluzole (Pittenger et al, 2015), and the NMDA receptor antagonist, memantine (Modarresi et al, 2018), have shown benefit as augmentation strategies in patients with SSRI-refractory OCD. Apart from its role in GABAglutamate signaling, EAAT3 also mediates cysteine uptake necessary for neuronal glutathione (GSH) production, thereby regulating cellular redox status.…”
Section: A Probing the Role Of Neurotransmitters In Obsessive-compulsive Disordermentioning
confidence: 91%